Indirect detection of 5-hydroxytryptamine and tyramine by using tris(2,2’-bipyridyl)ruthenium-graphene modified electrode coupled with capillary electrophoresis - Zhao, Zi Wei; Li, Fan Lin; Su, Ming (European Journal of Chemistry, 2019)
A highly sensitive and stable solid-state electrochemiluminescence (ECL) sensor was developed based on tris(2,2’-bipyridyl)ruthenium(II) (Ru(bpy)32+) integrating with 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) functionalized graphene. Ru(bpy)32+ is incorporated with the ABTS functionalized graphene based on not only the π-π stacking but also electrostatic interactions. Coupled with capillary electrophoresis (CE), this ECL sensor was used to detect tyramine and 5-hydroxytryptamine (5-HT) based on their quenching effects for the Ru(bpy)32+/tripropylamine (TPA) system. The quenching mechanism was illustrated and the conditions for CE separation and ECL detection were optimized. Based on an S/N = 3, the limit of detection (LOD) for tyramine and 5-HT were 0.1 μM and 0.02 μM, respectively. The applicability of the proposed method was further illustrated in the determination of tyramine and 5-HT in human plasma samples from small intestine carcinoid patients.